Omega 3 fatty acid inhibition of inflammatory cytokine-mediated Connexin43 regulation in the heart - Baum, Jennifer R.; Dolmatova, Elena; Tan, Alex; Duffy, Heather S. (Frontiers in Physiology, 2012)
Background: The proinflammatory cytokine Interleukin-1β (IL-1β), which increases in the heart post myocardial infarction (MI), has been shown to cause loss of Connexin43 (Cx43) function, an event known to underlie formation of the arrhythmogenic substrate. Omega 3 Fatty acids exhibit antiarrhythmic properties and impact IL-1β signaling. We hypothesize that Omega-3 fatty acids prevent arrhythmias in part, by inhibiting IL-1β signaling thus maintaining functional Cx43 channels. Methods: Rat neonatal myocytes or Madin-Darby Canine Kidney Epithelial (MDCK) cells grown in media in the absence (Ctr) or presence of 30μM docosahexaenoic acid (DHA, an Omega-3 Fatty acid) were treated with 0.1μM activated IL-1β. We determined Cx43 channel function using a dye spread assay. Western blot and immunostaining were used to examine Cx43 levels/localization and downstream effectors of IL-1 β. In addition we used a murine model of myocardial infarction (MI) for 24 hours to determine the impact of an Omega-3 fatty acid enriched diet on Cx43 levels/localization post myocardial infarction. Results: IL-1β significantly inhibited Cx43 function in Ctr cells (200.9 +/- 17.7 μm [Ctr] vs. 112.8 +/- 14.9 μm [0.1uM IL-1β], p<0.05). However, DHA-treated cells remained highly coupled in the presence of IL-1β [167.9 +/- 21.9 μm [DHA] vs. 164.4 +/- 22.3 μm [DHA+0.1uM IL-1β], p<0.05, n=4). Additionally, western blot showed that IL-1β treatment caused a 38.5% downregulation of Cx43 [1.00au [Ctr] vs 0.615au (0.1μM IL-1β) which was completely abolished in DHA treated cells (0.935au [DHA] vs. 1.02au [DHA+0.1μM IL-1β), p<0.05, n=3]. Examination of the downstream modulator of IL-1β, NFκβ showed that while hypoxia caused translocation of NFκβ to the nucleus, this was inhibited by DHA. Additionally we found that a diet enriched in Omega-3 Fatty acids inhibited lateralization of Cx43 in the post-myocardial infarction murine heart as well as limited activation of fibroblasts which would lead to decreased fibr